2022
DOI: 10.3390/molecules27123718
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Damages to H1N1 Influenza Virus Caused by Vapor Essential Oils

Abstract: Influenza viruses are transmitted from human to human via airborne droplets and can be transferred through contaminated environmental surfaces. Some works have demonstrated the efficacy of essential oils (EOs) as antimicrobial and antiviral agents, but most of them examined the liquid phases, which are generally toxic for oral applications. In our study, we describe the antiviral activity of Citrus bergamia, Melaleuca alternifolia, Illicium verum and Eucalyptus globulus vapor EOs against influenza virus type A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Electron microscopy revealed that thymol disrupted the envelope of HSV‐1 (Lai et al, 2012). Furthermore, an envelope of H1N1 influenza virus was partially decomposed after exposure to vapours of bergamot essential oil and destroyed after exposure to tea tree essential oil (Madia et al, 2022). It is, therefore, very likely that the destruction of the CyHV‐3 envelope might be the mechanism for virucidal activity of TEO.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy revealed that thymol disrupted the envelope of HSV‐1 (Lai et al, 2012). Furthermore, an envelope of H1N1 influenza virus was partially decomposed after exposure to vapours of bergamot essential oil and destroyed after exposure to tea tree essential oil (Madia et al, 2022). It is, therefore, very likely that the destruction of the CyHV‐3 envelope might be the mechanism for virucidal activity of TEO.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence from in vitro and animal studies proves that EOs have multiple biological activities, such as anticancer [ 4 , 5 ], antiviral [ 6 , 7 , 8 , 9 ], antibacterial [ 10 , 11 , 12 , 13 ], antifungal [ 14 , 15 ], antibiofilm [ 16 , 17 , 18 ], anti-inflammatory [ 19 , 20 , 21 ], and antioxidant [ 19 , 22 , 23 , 24 , 25 ] effects, which constitute the starting point for the in vivo assessment of those properties in various therapeutic and cosmetic fields [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Nevertheless, since great consideration has been given to the effective use of EOs in clinical procedures, further systematic animal studies and clinical investigations are needed.…”
Section: Introductionmentioning
confidence: 99%